Child Care in Times of COVID-19: Predictors of Distress in Dutch Children and Parents When Re-entering Center-Based Child Care After a 2-Month Lockdown - de Vet, Sanne M.; Vrijhof, Claudia I.; van der Veek, Shelley M. C.; Pieplenbosch, Jane M.; van Bakel, Hedwig J. A.; Vermeer, Harriet J. (Frontiers in Psychology, 2021)
As a consequence of the outbreak of the Coronavirus Disease 2019 (COVID-19) child care facilities all over the world were temporarily closed to minimize the spread of the virus. In the Netherlands, the first closure lasted for almost 2 months. The return to the child care center after this significant interruption was expected to be challenging, because earlier studies demonstrated that transitions into child care can be stressful for both children and their parents. The current paper retrospectively examined the distress of Dutch children (aged 0-4) and their parents during the first two weeks after the reopening of child care centers, and what factors accounted for individual differences in distress. In total, 694 parents filled out an online questionnaire about stress during closure and distress after the reopening of child care centers. Furthermore, questions regarding several demographic variables and child care characteristics were included, as well as questionnaires measuring child temperament, parental separation anxiety, and parental perception of the child care quality. Results showed that younger children and children with parents scoring higher on separation anxiety experienced more distress after the reopening, as reported by parents. Furthermore, children were more distressed upon return when they attended the child care center for less hours per week after the reopening, experienced less stress during closure, and grew up in a one-parent family. With regard to parental distress after the reopening, we found that parents scoring higher on separation anxiety and fear of COVID-19 experienced more distress. Moreover, parents experiencing less stress during closure and mothers were more distressed when the child returned to the child care center. Finally, concurrent child and parental distress after reopening were positively related. The results of the current study may help professional caregivers to identify which children and parents benefit from extra support when children return to the child care center after an interruption. Especially the role that parental separation anxiety played in predicting both child and parental distress deserves attention. More research is required in order to study the underlying mechanisms of these associations and to design appropriate interventions.